Interrogating identity - Phillips, Meredith L.; Grey Art Gallery & Study Center (Grey Art Gallery and Study Center, New York University, 1991)
Exposition collective regroupant : Araeen, Rasheed, 1935- ; Belmore, Rebecca, 1960- ; Chan, Nadine ; Chong, Albert ; DeSouza, Allan, 1958- ; Hassan, Jamelie, 1948- ; Hatoum, Mona, 1952- ; Kempadoo, Roshini ; Ligon, Glenn, 1960- ; Lovell, Whitfield, 1959- ; Maestro, Lani, 1957- ; Mulero, Lillian, 1950- ; Mur-Ray, Ming ; Piper, Keith, 1960- ; Pollard, Ingrid, 1953- ; Rodney, Donald, 1961-1998 ; Shonibare, Yinka, 1962- ; Simmons, Gary.
Keywords: arts; cours; discipline; har4610; histoire de l'art; identités culturelles; premier cycle